Implementation of the Project for Strengthening Pancasila Student Profiles in Shaping Student Character at Patriot Puturuh Vocational School - Purworejo - Wibowo, Muchammad Muchlas; Benny Kurniawan; Atim Rnawati; Moh. Agus Salim; Mahfud, Ali; Sukataman (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
The Pancasila Student Profile Strengthening Project (P5) is a project that aims to strengthen student character and competency. It is hoped that by implementing P5 in schools, teachers and school stakeholders will be able to create and produce a generation that has character. This research aims to analyze the implementation of P5 at Patriot Puturuh Vocational School in shaping the character of its students. This research is qualitative research, where data mining is carried out through interviews, observation and documentation. The validity of the data in early research was carried out by triangulating the data and checking the data again. The research was conducted at Patriot Pituruh Vocational School with research subjects, school principals, teachers, students and other stakeholders related to the research. The research results explain that the implementation of P5 can shape the character of vocational school students with several activity projects carried out. This is proven by the enthusiasm of students to take part.